2019
DOI: 10.1021/acs.organomet.9b00216
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Asymmetric C–H Bond Activation for the Synthesis of P-Stereogenic Dibenzophospholes

Abstract: Pd-catalyzed asymmetric C−H bond activation for the synthesis of P-stereogenic dibenzophospholes was efficiently achieved via two types of catalytic systems. Chiral phosphoric amides/acids as ligands provided the products with up to 5:95 er, and (R)-segphos as ligand resulted in enantioselectivities of up to 98:2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 57 publications
0
24
0
1
Order By: Relevance
“…[79] In addition to using SegPhosa sachiral ligand for the synthesis of P-stereogenic compounds through aryl desymmetrization (see Scheme 34), Duan and co-workersr eported the use of ac hiral base in combination with an achiral phosphine (Scheme 48). [94] They observed high levels of stereoinduction for unsubstitutedB INOL-derived acids and amides in combination with the well-defined Pd(PCy 3 ) 2 complex, and showed that, in this case, increasing the sterich indranceo nt he bi-naphthyl scaffold had an egative impact on the enantioselectivity.F urthermore, the phosphine ligand did not have am ajor influence on the enantioselectivity,a sa ne .r.o f9 1:9w as observed when using Pd(CH 3 CN) 2 Cl 2 as the Pd source and without added phosphine. Further optimization of the reaction conditions showedt hat a1 :1 combination of A 3 and A 8 resulted in as ignificant enhancement of the enantioselectivity,a nd that the catalyst loading could be reduced.…”
Section: Chiral Basesmentioning
confidence: 96%
See 2 more Smart Citations
“…[79] In addition to using SegPhosa sachiral ligand for the synthesis of P-stereogenic compounds through aryl desymmetrization (see Scheme 34), Duan and co-workersr eported the use of ac hiral base in combination with an achiral phosphine (Scheme 48). [94] They observed high levels of stereoinduction for unsubstitutedB INOL-derived acids and amides in combination with the well-defined Pd(PCy 3 ) 2 complex, and showed that, in this case, increasing the sterich indranceo nt he bi-naphthyl scaffold had an egative impact on the enantioselectivity.F urthermore, the phosphine ligand did not have am ajor influence on the enantioselectivity,a sa ne .r.o f9 1:9w as observed when using Pd(CH 3 CN) 2 Cl 2 as the Pd source and without added phosphine. Further optimization of the reaction conditions showedt hat a1 :1 combination of A 3 and A 8 resulted in as ignificant enhancement of the enantioselectivity,a nd that the catalyst loading could be reduced.…”
Section: Chiral Basesmentioning
confidence: 96%
“…In addition to using SegPhos as a chiral ligand for the synthesis of P‐stereogenic compounds through aryl desymmetrization (see Scheme 34), Duan and co‐workers reported the use of a chiral base in combination with an achiral phosphine (Scheme 48). [94] They observed high levels of stereoinduction for unsubstituted BINOL‐derived acids and amides in combination with the well‐defined Pd(PCy 3 ) 2 complex, and showed that, in this case, increasing the steric hindrance on the binaphthyl scaffold had a negative impact on the enantioselectivity. Furthermore, the phosphine ligand did not have a major influence on the enantioselectivity, as an e.r.…”
Section: Chiral Bases and Bifunctional Ligandsmentioning
confidence: 98%
See 1 more Smart Citation
“…To avoid the consumption of stoichiometric amounts of chiral reagents, asymmetric catalytic methods such as metal-catalyzed asymmetric couplings [12][13][14][15][16][17][18][19][20] and desymmetrization of prochiral phosphorus molecules have been developed. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Particularly, desymmetrization methods have been a more focus lately. Typical examples include transition metalcatalyzed intra-and intermolecular C-H functionalization, [22][23][24][25][26][27][28] Mo-and Ru-catalyzed ring-closing metathesis, 29,30 Rh-catalyzed cycloaddition and hydroarylation, 31,32 Au-catalyzed intramolecular hydroetherification, 33 Nheterocyclic carbene (NHC)-catalyzed esterification, 34 Tm-catalyzed intermolecular sulfenylation, 35 and cinchona alkaloid-catalyzed allylic alkylation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…At the transition state of this step, both the ligand and the base are coordinated to the metal center. Therefore, a chiral ancillary ligand [5] and/or a chiral base [6,7] may be used to bring in stereocontrol over the reaction. To induce a more organized transition state, and thereby to provide higher enantioselectivities in challenging cases, we recently developed a new family of chiral bifunctional phosphine-carboxylate ligands (Scheme 1 a).…”
mentioning
confidence: 99%